Murder in the family eaudiobook A novel. - Hunter, Cara (HarperAudio, 2023)
ONE BODY. SIX EXPERTS. CAN YOU SOLVE THE CASE BEFORE THEY DO? Mega-bestselling British crime novelist Cara Hunter makes her big American debut with a wholly immersive thriller like none you've seen before: written as the teleplay of a true-crime documentary, it has the reader puzzling away, reviewing photos, maps, coroner's reports and other evidence as they read. The exciting multi-narrator audiobook features five actors telling the story from different perspectives. Can you tell who's lying? ""An excellent, wholly original whodunnit! You won't have read a mystery like this, and you'll be kept in the dark right to the end."" —Gilly MacMillan, bestselling author of The Long Weekend It was a case that gripped the nation. In December 2003, Luke Ryder, the stepfather of acclaimed filmmaker Guy Howard (then aged 10), was found dead in the garden of their suburban family home. Luke Ryder's murder has never been solved. Guy Howard's mother and two half-sisters were in the house at the time of the murder—but all swear they saw nothing. Despite a high-profile police investigation and endless media attention, no suspect was ever charged. But some murder cases are simply too big to forget... Now comes the sensational new streaming series Infamous, dedicated to investigating—and perhaps cracking—this famous cold case. Years later a group of experts re-examine the evidence – with shocking results. Does the team know more than they've been letting on? True crime lovers and savvy readers, you can review the evidence and testimony at the same time as the experts. But can you solve the case before they do?